Structural Characterization of B-DNA d(CGTGAATTCACG)2 in Complex with the Specific Minor Groove Binding Fluorescent Marker Hoechst 33342 - Hristina Sbirkova-Dimitrova; Rusi Rusew; Hristo Gerginov; Annie Heroux; Boris L. Shivachev (Crystals)
Recently, there have been numerous reports on the use of different fluorescent DNA stains for specific minor groove binding. The exploration of biological markers increases the safety of their use as diagnostic criteria. Single crystal analysis of DNA–ligand binding interactions is of essential importance to obtain the requirements for their usage in the pharmaceutical and medical industries. Dyes that bind to DNA, such as Hoechst 33342 or 4′,6-diamidino-2-phenylindole (DAPI), can be used not only for analytical use, but for medical purposes. DAPI and Hoechst 33342 are fluorescent dyes that bind to the minor groove of DNA, fluorescing brightly in the blue region with an emission maximum at approximately 461 nm when excited by ultraviolet light (~350 nm). This work focuses on the binding interactions of Hoechst 33342 with the specific DNA sequence d(CGTGAATTCACG)2. The structure of the complex was determined using single-crystal X-ray diffraction at a resolution of 1.9 Å in the space group P212121. The coordinates and structure factors are deposited in the RCSB Protein Data Bank (PDB) under entry 9FT8. The structure is nearly isomorphous with that of previously reported crystal structures of the oligonucleotide d(CGTGAATTCACG)2 alone (PDB ID: 5JU4) and with that in complexes with DAPI (5T4W). The adjustments in crystal interactions between the native DNA molecule and the DNA–DAPI complex are described. Hoechst 33342 selectively binded to the tight minor groove close to the midpoint of the B-DNA segment, adjacent to the A–T base pairs. It interacted with DNA through hydrogen bonding and van der Waals forces. The structural comparison revealed that Hoechst 33342 inserts itself in the minor groove in a strongly specific manner, displacing the ordered spine waters.